Exploring language proficiency gaps: a syntactic error analysis - Hassanuzin, Salsabilla; Saaidi, Nur Suhaila; Khalil, 'Ammar; Jatin, Norhazwanie (Asian Scholars Network, 2025)
This study identifies common writing errors among 180 students in a matriculation center in Gambang, Pahang, Malaysia. It further explores a more specific aspect of writing at the syntactic level where students produce more errors in their essays. Through a mixed-method approach, descriptive analyses were conducted to assess errors in a writing task where students were required to write an opinion-based essay. The writing errors were identified based on the writing criteria that students were assessed in, which were task fulfilment, cohesion and coherence, vocabulary and language accuracy. Among these, students recorded the highest frequency of errors in the language aspect. Further investigation indicates that students primarily struggle with syntactic errors, particularly in complex and simple sentences. These results underscore the importance of targeted interventions in syntax to enhance writing proficiency among pre-university students.